2020
DOI: 10.1097/meg.0000000000001822
|View full text |Cite
|
Sign up to set email alerts
|

Risk of recurrent hepatic encephalopathy in patients with liver cirrhosis: a German registry study

Abstract: Background and aims Patients with hepatic encephalopathy (HE) show low quality of life, recurrent hospitalizations and an increased mortality. We aimed to assess the natural course of patients after a recent episode of overt HE and to identify risk factors for HE recurrence in Germany. Methods Fifteen sites took part in a prospective, observational study including patients with liver cirrhosis who had been hospitalized for HE within 3 months before recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…20 A small German study reported that 43.6% of 78 patients with a previous hepatic encephalopathy-related hospitalization were readmitted for hepatic encephalopathy; a history of ≥ 4 prior episodes of hepatic encephalopathy was identified as a risk factor for hepatic encephalopathy-related readmission (P < .001). 23 Hepatic Encephalopathy-Related Mortality. In contrast to data showing both increased admissions and readmissions for hepatic encephalopathy, [18][19][20][21]23 data from the NIS showed that in-hospital hepatic encephalopathy-related mortality, though substantial, has decreased significantly from 2009 to 2013 (11.9%-10.2%, respectively; P < .001).…”
Section: Outcomes In Patients With Hepatic Encephalopathymentioning
confidence: 99%
See 1 more Smart Citation
“…20 A small German study reported that 43.6% of 78 patients with a previous hepatic encephalopathy-related hospitalization were readmitted for hepatic encephalopathy; a history of ≥ 4 prior episodes of hepatic encephalopathy was identified as a risk factor for hepatic encephalopathy-related readmission (P < .001). 23 Hepatic Encephalopathy-Related Mortality. In contrast to data showing both increased admissions and readmissions for hepatic encephalopathy, [18][19][20][21]23 data from the NIS showed that in-hospital hepatic encephalopathy-related mortality, though substantial, has decreased significantly from 2009 to 2013 (11.9%-10.2%, respectively; P < .001).…”
Section: Outcomes In Patients With Hepatic Encephalopathymentioning
confidence: 99%
“…23 Hepatic Encephalopathy-Related Mortality. In contrast to data showing both increased admissions and readmissions for hepatic encephalopathy, [18][19][20][21]23 data from the NIS showed that in-hospital hepatic encephalopathy-related mortality, though substantial, has decreased significantly from 2009 to 2013 (11.9%-10.2%, respectively; P < .001). 14 The mean length of hospitalization was also significantly reduced, from 7.5 days (2009) to 7.1 days (2013; P = .02).…”
Section: Outcomes In Patients With Hepatic Encephalopathymentioning
confidence: 99%
“…There was no 11 ; thus, preventing complications is critical. Results of a previous study showed that 44% of patients with cirrhosis who developed OHE were rehospitalized within 1 year 12 ; further, survival rates decreased within a short time frame (42% survival at 1 year; 23% at 3 years). 13 The changes observed with rifaximin SSD IR 40 mg vs placebo might underscore the role of GI microbial modification in cirrhosis progression that may be agnostic of etiology.…”
Section: Discussionmentioning
confidence: 90%
“…Assessments. Efficacy and safety assessments were conducted at Day 1 (baseline) and Weeks 2,4,8,12,16,20, and 24 (end of treatment); all patients completed an end-of-study assessment at Week 26 (or time of early termination). The primary efficacy endpoint, per protocol, was time to hospitalization due to a cirrhosis-related complication (hepatic encephalopathy [HE], EVB, hepatorenal syndrome, or SBP) or all-cause mortality during 24 weeks of treatment; no interim analysis was performed.…”
Section: Trial 1: Rnlc2131 (Prevention Of Cirrhosis Complications Trial)mentioning
confidence: 99%
“…The PHES consists of 5 paper-pencil tests evaluating cognitive/psychomotor processing speed and visuomotor coordination. They are relatively easy to administer, have good external validity and have been translated/validated into several languages and countries 251. Animal naming test (ANT)Neuropsychological, bed-side The ANT (i.e.…”
mentioning
confidence: 99%